Employment of people living with HIV in the province of Buenos Aires (Actualizaciones en Sida e Infectología, 2021)
One of the variables to measure the quality of life of people living with the Human Immunodeficiency Virus (HIV) is labour. The objective was to compare the labour situation of people living with the HIV in Buenos Aires discriminating by gender. Comparative study in 3 hospitals between April and July 2015. The following were evaluated: age range, idg, antiretroviral treatment, viral load, dependents, self-perception of health status, educational level, work situation, access to social benefits, comparison between income and minimum wage, occupation. α=5% to two queues. Mann-Whitney-Wilcoxon and Fisher tests were conducted. 82 surveys were performed. 87.2% between 20 and 59 years old; male (M)/female (F) ratio: 1/1; 84.1% under antiretroviral treatment and 67.1% had undetectable viral load. 54.9% with dependents. The median self-perception of health was 7.94 with no differences between sexes (p=0.35). 48.8% of the M and 50% of the F had at most 7 years of formal education. 17.1% of the men and 7.5% of the women were unemployed (p=0.03); informal work accounted for 65.8% of the men and 37.5% of the women, but 47.5% of the women were housewives. 32.9% of the people do not receive social benefits, 20% of F and 43.9% of M (p=0.03). The income of the people corresponded to 64.8% of the minimum wage. The economic situation of the country has changed, and it remains to be seen if the employment situation has changed as well.
Keywords: Employment; HIV; Gender equality